Open access to research data in brazil: Mapping repositories, practices and perceptions of researchers and technologies - Gabriel Junior, Rene Faustino [UNESP]; da Rocha, Rafael Port; Caregnato, Sônia Elisa; Pavão, Caterina Marta Groposo; Passos, Paula Caroline Schifino Jardim; Borges, Eduardo Nunes; Vanz, Samile Andréa de Souza; Azambuja, Luís Alberto Barbosa (My University, 2019)
Initiatives to promote Open Access to Research Data have grown significantly worldwide, although in Brazil there are still few studies on the subject. The aim of this paper is to present the development and results of the project RDP Brasil, developed in a partnership between RNP, IBICT, UFRGS, and FURG. The project, which has been under development since March 2018, has been divided into five stages: mapping of practices and of services in Brazilian institutions; assembling of the community to discuss the topic through a web portal; survey of existing technology for sharing data; and development of a technology solution to meet the requirements of a selected group of users. The results show that institutional initiatives for open research data sharing in Brazil are still few; that Brazilian researchers are motivated by the idea of data sharing and reuse, but there is a lack of knowledge and poor institutional infrastructure; that existing technologies offer a large number of options and should therefore be constantly monitored; and that developing data repository pilots is a viable solution in the short term. It is concluded that the project was a pioneer in investigating Brazilian researchers from all areas of knowledge about Open Access to Research Data in Brazil, bringing relevant contributions to emerging government initiatives, such as Brazil’s commitment to the Open Government Partnership initiative. However, there is still a need to expand research on the subject and make public efforts to promote new and consolidate existing initiatives.
Acceso abierto a datos de investigación en brasil: Mapeo de repositorios, prácticas y percepciones de investigadores y tecnologías
Acesso aberto a dados de pesquisa no brasil: Mapeamento de repositórios, práticas e percepções dos pesquisadores e tecnologias
Keywords: Data reuse; Data sharing; Open access to research data; Research data repository; Software